Lithium manganese iron phosphate composite positive electrode particles
Coating LMFP particles with a conductive layer of lithium-ion conductor particles and carbon aggregates addresses conductivity and degradation issues, enhancing battery performance through improved lithium ion transport and stability.
Patent Information
- Application Number
- JP2024003991U
- Authority / Receiving Office
- JP · JP
- Patent Type
- Utility models
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2034-11-29
AI Technical Summary
Lithium manganese iron phosphate (LMFP) positive particles exhibit low magnification charging/discharge performance, poor lithium ion conductivity, and rapid degradation, limiting their effectiveness in batteries.
Coating LMFP particles with a conductive layer composed of multiple lithium-ion conductor particles and carbon aggregates enhances conductivity and lithium ion mobility, forming a composite positive particle structure.
The composite structure improves battery performance by increasing conductivity and lithium ion transport, leading to enhanced charging and discharging capabilities and reduced degradation.
Smart Images

Figure 0003250000000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a battery positive electrode material, and more particularly to a lithium manganese iron phosphate composite positive electrode particle. [Background technology]
[0002] A battery is composed of a positive electrode and a negative electrode, and the negative electrode of the battery is the positive electrode inside the battery. The positive electrode of a general all-solid-state or semi-solid battery mainly comprises a positive electrode substrate and a positive electrode slurry layer, and the positive electrode slurry layer includes a positive electrode slurry and positive electrode particles. The positive electrode particles need to have auxiliary electrical conductivity or electrical conductivity so that free electrons can move in the positive electrode slurry and avoid excessive energy consumption due to internal resistance. As the material of the positive electrode particles, LMFP (lithium manganese iron phosphate) may be selected, which has better operating voltage performance than lithium iron phosphate (LFP), releases at a higher energy density, is low-cost, and has hydrophobicity. Summary of the Invention [Problem to be solved by the invention]
[0003] However, LMFP has low multiplier charge / discharge performance, low lithium guiding ability and low conductive ability, and its structure quickly deteriorates when used in a battery for a long time. Although there are already many technologies to improve the guiding ability of the positive electrode particles for lithium ions, their conductive ability is still insufficient for practical use.
[0004] Therefore, as a result of intensive research, the present inventors have found that the above object can be achieved by providing a positive electrode of an all-solid-state battery with higher capacity and conductivity.
[0005] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide lithium manganese iron phosphate composite positive electrode particles.
[0006] In order to solve the above problems, the present invention adopts the following measures. In one embodiment of the present invention, the lithium manganese iron phosphate composite positive electrode particles are coated with a conductive layer on the outside of the LMFP particles to improve the overall performance. The cost of LMFP is lower than that of ternary oxides, and its charge / discharge performance is applicable to a certain range, so that using it as a positive electrode material can reduce the manufacturing cost of batteries. The conductive layer coating the outer surface of the LMFP particles can make up for the shortcoming of LMFP's low electrical conductivity, and the outer surface of the LMFP particles is further coated with a plurality of lithium ion conductor particles to improve the overall lithium ion guide ion ability, while also improving the overall electrical conductivity and lithium ion guide ion ability, thereby achieving a better battery effect.
[0007] At least the following points will become apparent from the following specification and drawings. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 is a schematic cross-sectional view of a composite positive electrode particle according to an embodiment of the present invention. [Diagram 2] 1 is an embodiment of the lithium manganese iron phosphate composite positive electrode particles according to the present invention. [Diagram 3] 1 is a schematic diagram and an enlarged view of a composite positive electrode particle according to an embodiment of the present invention; [Figure 4] FIG. 2 is a schematic diagram showing a composite positive electrode particle coated with a carbon material according to an embodiment of the present invention. [Diagram 5] 1 is a schematic diagram showing the configuration of a lithium ion composite conductor particle according to an embodiment of the present invention; [Figure 6] 2 is another embodiment of the lithium ion composite conductive particles according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described below through the embodiments of the invention, but the following embodiments do not limit the invention according to the claims. In addition, not all of the combinations of features described in the embodiments are necessarily essential to the solution of the invention.
[0010] First, with reference to Figs. 1 to 6, an embodiment of the lithium manganese iron phosphate composite positive electrode particle according to the present invention will be described.
[0011] The lithium manganese iron phosphate composite positive electrode particles according to the present invention are used in a positive electrode 100 of an all-solid-state or semi-solid battery. The positive electrode 100 mainly includes a positive electrode substrate 105 (see FIG. 2) and a positive electrode slurry layer 108 coated on the positive electrode substrate 105. The positive electrode slurry layer 108 includes a positive electrode slurry 103 having a binder and a plurality of composite positive electrode particles 200. The weight percent of the total weight of the plurality of composite positive electrode particles 200 in the positive electrode slurry layer 108 is in the range of 88 wt% to 98 wt%.
[0012] 1 shows the composition of each composite positive electrode particle 200 according to an embodiment of the present invention, which mainly includes the following components:
[0013] The LMFP particles 121 have a D50 particle size (mass-median-diameter, MMD, the mass median diameter of the particle size distribution) of less than 1 μm and are either single crystal materials or polymers of finely crystalline particles.
[0014] The LMFP particles 121 are lithium manganese iron phosphate (LiMn x Fe 1-x PO4, where x is in the range of 0.1 to 0.8) or lithium manganese ferric phosphate doped with at least one metallic element.
[0015] The outer surface of the LMFP particle 121 is coated with a conductive layer 122 to form the overall composite cathode particle 200, the conductive layer 122 including a plurality of carbon aggregates 123 and a plurality of lithium ion conductor particles 10 for enhancing electrical conductivity (see FIG. 1). Each of the carbon aggregates 123 is formed from a carbon source that is added during the processing of the composite cathode particle 200.
[0016] The carbon aggregates 123 of the conductive layer 122 can form organic compounds of carbon in a reducing atmosphere. The organic compounds are selected from carbohydrates (e.g., monosaccharides, disaccharides, oligosaccharides, polysaccharides), water-soluble fibers, and amino acid polymers. Preferably, the organic compounds are compounds containing carbon and elements such as nitrogen, fluorine, phosphorus, and sulfur, and these elements are doped into carbon after a reduction reaction occurs to increase the electronic conductivity of the entire composite positive electrode particle 200.
[0017] The plurality of carbon aggregates 123 of the conductive layer 122 are a plurality of carbon aggregates formed by dehydrating carbohydrates, a carbon aggregate formed by dehydrating water-soluble fibers and including a plurality of carbon skeletons and partial functional groups, or a carbon aggregate formed by dehydrating amino acid polymers and including a plurality of carbon skeletons having straight or branched side chains of dopants.
[0018] The conductive layer 122 further includes a plurality of conductive carbons 124 for connecting the carbon aggregates 123 and allowing electrons to cross different carbon aggregates 123 through the conductive carbons 124, thereby enhancing overall conductivity. The conductive carbons 124 are made of one of graphite, graphene, nano-sized amorphous carbon, or carbon nanotubes having a length of 1 μm or less (see FIG. 6).
[0019] The lithium ion conductor particles 10 are distributed inside the conductive layer 122, adjacent to the outside of the conductive layer 122, or adjacent to the outer surface of the LMFP particle 121. The conductive layer 122 has a thickness of 200 nm or less. The size of each of the lithium ion conductor particles 10 is 200 nm or less.
[0020] The lithium ion conductor particles 10 have a lithium ion conducting ability (ionic conductivity of 10 -5 cm 2The oxides or carbonates having lithium ion conducting capability are, for example, lithium aluminum titanium phosphate (LATP) having a NASICON (sodium (Na) super ionic conductor) structure, lithium aluminum germanium phosphate (LAGP), or phosphates such as lithium phosphate (Li3PO4) having lithium conducting capability. The oxides having a garnet or perovskite structure are, for example, lithium lanthanum zirconium oxide (Li7La3Zr2O 12 The lithium ion conductor particles 10 may be a combination of the above-mentioned components in any ratio.
[0021] The outer surface of each of the lithium ion conductor particles 10 may be further coated with a boric acid layer 5 to form a lithium ion composite conductor particle 101. The distribution morphology of each of the lithium ion composite conductor particles 101 in the LMFP particle 121 may be a continuous distribution morphology, a discontinuous distribution morphology, or an island particle morphology, which is a structure that is naturally formed during the process.
[0022] The purpose of coating the outer surface of the lithium ion conductor particle 10 with the boric acid layer 5 is that in the manufacturing process of the composite positive electrode particle 200, in an oxygen-free sintering environment, the lithium in the lithium ion conductor particle 10 becomes deficient due to oxygen deficiency, resulting in a decrease in conductivity. By coating the outer surface of the lithium ion conductor particle 10 with the boric acid layer 5 to serve as a protective layer, the structure of the lithium ion conductor particle 10 is prevented from being destroyed.
[0023] Each of the lithium ion conductor particles 10 is formed of an LLZO material, which is formed of at least one of LLZO, Ga-LLZO (Ga-doped LLZO, gallium-doped lithium lanthanum zirconium oxide), Cu-LLZO (Cu-doped LLZO, copper-doped lithium lanthanum zirconium oxide), Ta-LLZO (Ta-doped LLZO, tantalum-doped lithium lanthanum zirconium oxide), Sr-LLZO (Sr-doped LLZO, strontium-doped lithium lanthanum zirconium oxide), and Al-LLZO (Al-doped LLZO, aluminum-doped lithium lanthanum zirconium oxide).
[0024] Preferably, the LLZO material is Cu a ,X b -LLZO, a ,X b -LLZO is lithium lanthanum zirconium oxide doped with copper and element X, where X is selected from gallium (Ga), tantalum (Ta), strontium (Sr), barium (Ba), and aluminum (Al), and a>0 and b>0. Preferably, a+b=0.25-0.8, and a>0.1. Although the technique of doping LLZO with copper is very difficult, the overall structure is more stable, the lithium ion channel is more smooth, the sintering speed is improved, and the manufacturing cost is very low. In addition, when the LLZO material is exposed to air, the formation of lithium carbonate (Li2CO3) is reduced, that is, the surface stability of the entire material is improved during sintering.
[0025] When the lithium ion conductor particles 10 are made of LAGP or LATP, the LAGP or LATP is Li 1+x Al x A 2-x (PO4)3 or Li 1+x+y Al x A 2-x-y-z M y N z(PO4)3, where x is in the range of 0.1 to 0.8, y is in the range of 0 to 0.2, and z is in the range of 0 to 0.2. A is Ge (germanium) or Ti (titanium). M is Sc 3+ (Scandium ion), Y 3+ (Yttrium ion), Ga 3+ (Gallium ion), In 3+ (Indium ion), La 3+ (lanthanum ion) and other trivalent cations. N is Zr 4+ (zirconium ion), Si 4+ (Silicon ion), Sn 4+ (tin ion) and other tetravalent cations.
[0026] 4, the present invention enhances electrical conductivity by coating the outer surface of the composite positive electrode particle 200 with a carbon material. The carbon material includes a plurality of carbon nanotubes 40 (CNTs) and a plurality of nanoscale amorphous carbons 45, which coat the outer surface of the composite positive electrode particle 200 to form a composite positive electrode particle 280 coated with the carbon material.
[0027] The carbon nanotubes 40 according to the present invention include a plurality of short carbon nanotubes 42 and a plurality of long carbon nanotubes 44, and the length of each of the short carbon nanotubes 42 is in the range of 0.2 μm to 1 μm, and the length of each of the long carbon nanotubes 44 is in the range of 1 μm to 3 μm. The weight ratio of the short carbon nanotubes 42 and the long carbon nanotubes 44 is in the range of 10:1 to 2:1. The weight ratio of the total weight of the carbon nanotubes 40 and the total weight of the nano-scale amorphous carbon 45 is in the range of 1:1 to 1:10. The size of the nano-scale amorphous carbon 45 is in the range of 10 nm to 40 nm. The weight ratio of "the total weight of the carbon nanotubes 40 and the nano-scale amorphous carbon 45" and the total weight of the composite positive electrode particles 200 is less than 1:100, that is, the weight ratio value is less than 0.01.
[0028] The carbon nanotubes 40 of different lengths form bridges with different numbers of layers in the composite positive electrode particle 200. The short-chain carbon nanotubes 42 can bridge each of the lithium ion conductor particles 10 and the LMFP particles 121. The long-chain carbon nanotubes 44 are used to cover the entire composite positive electrode particle 200 to enhance the overall structural strength. When multiple carbon nanotubes 40 are attached to the composite positive electrode particle 200, a hairball shape is formed.
[0029] The advantage of the carbon nanotubes 40 is that lithium ions are easily stabilized between the carbon nanotubes 40, so the electrode slurry of the present invention is stabilized as a large number of lithium ions, which increases the overall conductivity of lithium ions, and electrons are easily fixed between the carbon nanotubes 40, which increases the overall conductivity of lithium ions. In addition, the extremely high ion conductivity helps the entire battery to be charged and discharged quickly.
[0030] The nanoscale amorphous carbon is, for example, a super P conductive material. The nanoscale amorphous carbon 45 and the carbon nanotubes 40 are both conductive materials. The nanoscale amorphous carbon 45 has a particle shape, and the carbon nanotubes 40 have an elongated shape. The nanoscale amorphous carbon 45 fills the gaps between the carbon nanotubes 40 that are crossed vertically and horizontally, and the nanoscale amorphous carbon 45 is bridged, so that charges are conducted to other carbon nanotubes 40, and the current transmission efficiency is further improved.
[0031] The present invention is not limited to the above-described embodiments, and various modifications are possible within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included in the technical scope of the present invention. [Explanation of symbols]
[0032] 5 Boric Acid Layer 10 Lithium ion conductor particles 40 Carbon Nanotubes 42 Short-Chain Carbon Nanotubes 44 Long-chain carbon nanotubes 45 Nanoscale amorphous carbon 100 positive electrode 101 Lithium-ion composite conductor particles 105 Positive substrate 103 Positive electrode slurry 108 Positive electrode slurry layer 121 LMFP particles 122 Conductive layer 123 Carbon Aggregates 124 Conductive Carbon 200 Composite Positive Electrode Particles 280 Composite Positive Electrode Particles Covering Carbon Materials
Claims
1. A lithium manganese iron phosphate composite positive electrode particle for use in a positive electrode of an all-solid-state or semi-solid-state battery, the composite positive electrode particle comprising: LMFP particles; and a conductive layer covering an outer surface of the LMFP particle, the conductive layer comprising a plurality of carbon aggregates and a plurality of lithium ion conductor particles; the plurality of lithium ion conductor particles are distributed within the conductive layer, adjacent to the exterior of the conductive layer, or adjacent to an outer surface portion of the LMFP particle; The lithium ion conductor particles are oxides or carbonates having lithium ion conducting ability, or oxides having a garnet or perovskite structure.
2. 2. The lithium manganese iron phosphate composite positive electrode particle of claim 1, wherein the carbohydrate is selected from the group consisting of monosaccharides, disaccharides, oligosaccharides, and polysaccharides.
3. The lithium ion conductor particles have an ionic conductivity of 10 -5 cm 2 The oxide or carbonate having a ionic conductivity of more than 1 / s includes lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP) having a NASICON (sodium (Na) super ionic conductor) structure, or a phosphate having lithium conducting ability. The lithium manganese iron phosphate composite positive electrode particle according to claim 1 .
4. 2. The lithium manganese iron phosphate composite positive electrode particle according to claim 1, wherein the oxide having a garnet or perovskite structure includes lithium lanthanum zirconium oxide (LLZO) or lithium lanthanum titanium oxide (LLTO).
5. 2. The lithium manganese iron phosphate composite positive electrode particle of claim 1, wherein the mass median particle size in the particle size distribution of the LMFP particles is less than 1 μm, and the morphology is a single crystal material or a polymer of microcrystalline particles.
6. The LMFP particles are lithium manganese iron phosphate (LiMnFe 1 -xPO 4 2. The lithium manganese iron phosphate composite positive electrode particle according to claim 1, characterized in that it is composed of lithium manganese iron phosphate doped with at least one metal element, or lithium manganese iron phosphate doped with at least one metal element.
7. The lithium manganese iron phosphate composite positive electrode particle according to claim 1, characterized in that the carbon aggregate is a compound containing carbon and elements such as nitrogen, fluorine, phosphorus, and sulfur, and the nitrogen, fluorine, phosphorus, and sulfur are doped into the carbon.
8. The lithium manganese iron phosphate composite positive electrode particle according to claim 1, characterized in that the outer surface of each of the lithium ion conductor particles is coated with a boric acid layer to form a lithium ion composite conductor particle, and each of the lithium ion composite conductor particles has a distribution form in the LMFP particle that is continuous, discontinuous, or island-like.
9. 2. The lithium manganese iron phosphate composite positive electrode particle of claim 1, wherein the conductive layer has a thickness of 200 nm or less, and the size of each of the lithium ion conductor particles is 200 nm or less.
10. 2. The lithium manganese iron phosphate composite positive electrode particle according to claim 1, wherein each of the lithium ion conductor particles is made of an LLZO material, and the LLZO material is made of at least one of LLZO, Ga-LLZO (Ga-doped LLZO, gallium-doped lithium lanthanum zirconium oxide), Cu-LLZO (Cu-doped LLZO, copper-doped lithium lanthanum zirconium oxide), Ta-LLZO (Ta-doped LLZO, tantalum-doped lithium lanthanum zirconium oxide), Sr-LLZO (Sr-doped LLZO, strontium-doped lithium lanthanum zirconium oxide), and Al-LLZO (Al-doped LLZO, aluminum-doped lithium lanthanum zirconium oxide).
11. Each of the lithium ion conductor particles is Cu a , X b -LLZO, and the Cu a , X b 2. The lithium manganese iron phosphate composite positive electrode particle according to claim 1, wherein LLZO is lithium lanthanum zirconium oxide doped with copper and element X, where X is selected from gallium (Ga), tantalum (Ta), strontium (Sr), barium (Ba), and aluminum (Al), and a>0 and b>0.
12. The lithium manganese iron phosphate composite positive electrode particles according to claim 11, characterized in that a+b=0.25-0.8, and a>0.
1.
13. Each of the lithium ion conductor particles is formed of LAGP or LATP, and the LAGP or LATP is 1+x A x A 2-x (P.O. 4 ) 3 Or Li 1+x+y A x A 2-x-y-z M y N z (P.O. 4 ) 3 2. The lithium manganese iron phosphate composite positive electrode particle according to claim 1, wherein x is in the range of 0.1 to 0.8, y is in the range of 0 to 0.2, z is in the range of 0 to 0.2, A is germanium (Ge) or titanium (Ti), M is a trivalent cation, and N is a tetravalent cation.
14. The lithium manganese iron phosphate composite positive electrode particle according to claim 1, characterized in that the outer surface of the composite positive electrode particle is further coated with a carbon material, the carbon material further comprises a plurality of carbon nanotubes and a plurality of nano-scale amorphous carbons, and the size of the nano-scale amorphous carbons ranges between 10 nm and 40 nm.
15. The lithium manganese iron phosphate composite positive electrode particle of claim 14, wherein the carbon nanotubes include a plurality of short chain carbon nanotubes and a plurality of long chain carbon nanotubes, the length of each of the short chain carbon nanotubes being in the range of 0.2 μm to 1 μm, and the length of each of the long chain carbon nanotubes being in the range of 1 μm to 3 μm.